2020
DOI: 10.1177/0043820020945683
|View full text |Cite
|
Sign up to set email alerts
|

Research Note: Governance Indicators Explain Discrepancies in COVID‐19 Data

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is neutral. It does not discriminate: the outbreak affects all countries. Yet, countries with better governance detect and report COVID-19 cases an average of 34 days earlier than countries with low governance scores. They also report a significantly higher number of cases, and more deaths but lower death-per-case ratios. Analyzing the statistical relationship between the good governance indicators devised by the World Bank with data pertaining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 21 publications
1
19
0
3
Order By: Relevance
“…Overall, we found that several aspects of governance quality impacted how well nations grappled with COVID-19, with government effectiveness have a particularly noteworthy influence. Our results also support both Baris and Pelizzo (2020) and Chien and Lin (2020) , whose WGI-based investigations found that good governance was an important factor for coping with COVID-19. In addition, our findings echo evidence reported by Liang et al.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, we found that several aspects of governance quality impacted how well nations grappled with COVID-19, with government effectiveness have a particularly noteworthy influence. Our results also support both Baris and Pelizzo (2020) and Chien and Lin (2020) , whose WGI-based investigations found that good governance was an important factor for coping with COVID-19. In addition, our findings echo evidence reported by Liang et al.…”
Section: Discussionsupporting
confidence: 86%
“…Using data reported by the Worldwide Governance Indicators (WGI) project, several have specifically examined the relationships between governance quality and COVID-19-related indices. For instance, Baris and Pelizzo (2020) reported that countries with better governance effectively confronted COVID-19 in a manner that reduced fatalities, while Chien and Lin (2020) found that better governance was generally associated with stronger national resilience to the pandemic. Meanwhile, studies by both Liang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Our first article this time continues debates in previous issues of the journal concerning the impact of the coronavirus disease 2019 (COVID-19) pandemic on world affairs (see, e.g., Baris and Pelizzo 2020; Kavalski 2021; Klimkin and Umland 2020)—this time from the perspective of soft power and public diplomacy. In “A Critical Juncture?…”
mentioning
confidence: 90%
“…3 The African Press 4 reported that as of December 19, 2020, there have been 2,469,099 cases and nearly 60,000 deaths in Africa. If the data are to be trusted (see Baris and Pelizzo 2020 ), Africa was hit by the pandemic, but not as much as other regions. The economic consequences of COVID-19 in the continent are not as dire as they have been and are going to be for other regions.…”
Section: The Economic Consequences Of Covid-19mentioning
confidence: 99%